Potensi Simpanan Karbon Sistem Agroforestri Kopi Arabika Gayo Sebagai Upaya Mitigasi Perubahan Iklim di Kabupaten Bener Meriah - Halus Satriawan; Dedi Rahman; Ernawita (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Climate change poses a growing threat to global coffee production, while agroforestry systems are increasingly recognized for their ecological and economic benefits, including their potential to enhance carbon sequestration. This study aimed to analyze the carbon stock of the Gayo coffee agroforestry system in Bener Meriah Regency. Field data were collected using a purposive sampling approach based on canopy density and accessibility, covering 16 plots measured between July and September 2024. Carbon estimation was conducted using the RaCSA method developed by ICRAF. The results show that Gayo coffee agroforestry represents a complex system with diverse plant species contributing to carbon storage. The highest carbon stock is recorded for Petai (Parkia speciosa) at 28.98 ton C/ha, while the lowest occurs in red chili (Capsicum annuum L.) at 0.034 ton C/ha. The total measured carbon stock reaches 2,115.072 ton C, with an average of 124.416 ton C/ha. These findings demonstrate that the Gayo coffee agroforestry system provides a substantial contribution to climate change mitigation through aboveground carbon storage. The study concludes that enhancing agroforestry-based coffee farming has ecological and economic benefits and strengthens opportunities for implementing low-carbon agricultural certification and social forestry programs. Future research may further explore belowground carbon and long-term carbon dynamics across different management intensities.